Efektivitas Membran Zeolit-Silika untuk Penyisihan Total Suspended Solids (TSS) pada Limbah POME - Sari, Tika Kumala (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Filtration membranes using natural zeolite and silica sand materials can be a promising alternative filtration technology for processing palm oil industrial wastewater. Palm oil wastewater is waste produced by the palm oil industry that contains high TSS content and will pollute the aquatic environment if not optimally treated. This study aims to determine the effectiveness of TSS removal in palm oil wastewater using zeolite-silica membranes. Membrane performance was evaluated through filtration tests using a cross-flow reactor for 100 minutes, with permeate samples taken every 20 minutes at a pressure of 5 bar. Membrane performance was assessed based on membrane flux values and TSS rejection rates. The results showed that the initial TSS characteristics of palm oil wastewater at a 100% concentration were 3,180 mg/L, while at a 50% concentration, they were 1,120 mg/L. The highest TSS removal efficiency was achieved at a 100% wastewater concentration, reached 92.1%